2021
DOI: 10.3390/polym13213738
|View full text |Cite
|
Sign up to set email alerts
|

Colour Fastness to Various Agents and Dynamic Mechanical Characteristics of Biocomposite Filaments and 3D Printed Samples

Abstract: The aim of the study was to analyse the colour fastness of 3D printed samples that could be used as decorative or household items. Such items are often fabricated with 3D printing. The colour of filaments affects not only the mechanical properties, but also the appearance and user satisfaction. Samples of biocomposite filaments (PLA and PLA with added wood and hemp fibres) were used. First, the morphological properties of the filaments and 3D printed samples were analysed and then, the colour fastness against … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 37 publications
(55 reference statements)
0
8
0
Order By: Relevance
“…Fillers with a lower surface area per volume or insufficient fibre–matrix surface interaction are known for allowing a greater mobility of the biocomposite, leading to increased heat dissipation under deformation through applied stress to the biocomposite. This results in a higher loss modulus, as seen for series 1/50/180 [ 52 , 53 , 54 ]. The greater chain mobility observed for series 1/50/180 was already indicated by its comparatively high MFI, thus confirming the presented results.…”
Section: Resultsmentioning
confidence: 85%
“…Fillers with a lower surface area per volume or insufficient fibre–matrix surface interaction are known for allowing a greater mobility of the biocomposite, leading to increased heat dissipation under deformation through applied stress to the biocomposite. This results in a higher loss modulus, as seen for series 1/50/180 [ 52 , 53 , 54 ]. The greater chain mobility observed for series 1/50/180 was already indicated by its comparatively high MFI, thus confirming the presented results.…”
Section: Resultsmentioning
confidence: 85%
“…Commercial composite filaments (PLA/hemp/wood fiber) and printed samples were studied for color fastness and dynamic mechanical analyses. [ 154 ]…”
Section: Fdm Compositesmentioning
confidence: 99%
“…Commercial composite filaments (PLA/hemp/wood fiber) and printed samples were studied for color fastness and dynamic mechanical analyses. [154] Compared to PLA and hemp composites, hemp composites (Filament and 3D samples) have demonstrated more excellent heat stability. Colorfastness was lowest in wood fiber composites.…”
Section: Effects Of Filler Percentage On Mechanical and Thermal Prope...mentioning
confidence: 99%
“…The expansion of the neck created between nearby fibers, as well as molecular diffusion and randomness at the interface, all affect the strength of these interactions [71]. In a recent study, Muck et al [72] developed a wood/PLA composite filament and found that the outer surface of the filament has a rough surface and a highly porous structure, as in Figure 9a,b. The filament has fiber pullouts, gaps between the fiber and the matrix, an extremely uneven transverse surface and structure, and a non-eccentric diameter.…”
Section: Morphology and Surface Qualitymentioning
confidence: 99%